Spatial characteristics of the massive MIMO channel based on indoor measurement at 1.4725 GHz. Issue 2 (23rd January 2018) - Lu, Yanping; Tao, Cheng; Liu, Liu; Liu, Kai
Abstract : Massive multiple‐input–multiple‐output (MIMO) is acknowledged as a key technology for the fifth generation of wireless communication systems, theoretically proved to be of higher throughput, better robustness, superior spectrum‐ and energy‐efficiency with a general presumption that the channels tend to pairwise orthogonal with the increasing of the asymmetrical antenna pairs. Recently, more and more researches have cast light on massive MIMO system modelling. However, few investigations have been done on spatial characteristics of massive MIMO systems, especially the systems equipped with more than 100 antennas. This study focuses on the massive MIMO channel spatial characteristics based on indoor line‐of‐sight radio propagation measurement at 1.4725 GHz, and extracts spatial parameters such as angle of arrival, angle of departure and power azimuth spectrum from experimental data. The angles of departure (AODs) show a linear decrease along the linear antenna array, which are in agreement with the simulation of the ray tracing. On the basis of the realistic results of angular spread and the Gaussian density model, the investigation proves that antenna elements are deeply correlated and the envelope correlation coefficients show negative exponential down‐trend with the increasing of antenna spacing in massive MIMO systems.